Mythos Eisenbahn. Vor 175 Jahren begann in Deutschland das Bahnzeitalter. - Haase, Ralf (Deutscher Verkehrs-Verl., 2010)
Die Geschichte der deutschen Eisenbahnen ist historisch gesehen ein Erfolgsmodell des modernen Verkehrs - regional, national und international. Regional, weil der frühe Bahnbau die Industrierevolution im politisch zersplitterten Deutschland stimulierte und die Reisewünsche der Menschen beflügelte. National, weil die Eisenbahnen im Verbund mit dem deutschen Zollverein schrittweise eine nationale Volkswirtschaft im deutschen Bund entstehen ließen. International, weil die Verknüpfung der entstehenden nationalen Netze zu ständig wachsender Mobilität von Gütern und Personen in Europa führte, Handel und Dienstleistungen förderte und den Wohlstand der Menschen vermehrte.

The commissioning of the first rail link between Nuremberg and Fürth on 7 December 1835, over a distance of some 6 km, launched the railway age in Germany. As a form of propulsion for vehicles, the use of steam power signified an encouragement for Germany's industrial revolution at a time when the economy had fallen behind and the nation was in a state of political disunity, while also offering support for an emerging national economy. After the first long haul rail service between Leipzig and Dresden had provided proof of its inherent usefulness and convenience, 1839 became the starting point for the construction of a railway system across Germany, and the creation of an all-German rail network that, in the wake of the foundation of the Reich in 1871 enjoyed its greatest extension by comparison with the rest of Europe. For the fact that the first rail link between Nuremberg and Fürth never achieved any form of economic significance, the far-sightedness and commitment of such notable personalities as Georg Zacharias Platner and Johannes Scharrer continue to demand the respect of our generation. The Deutsche Bahn AG upholds this legacy, and readily faces the requirement of remaining the pillar of Germany's entire transport system against the background of the completely changed social conditions of the 21st century. Simultaneously, it seeks to enhance its worldwide activities as a provider of efficient mobility and logistics-related services.
The railway mythos - the age of the railways began 175 years ago.
Keywords: Landesgeschichte; Verkehrswirtschaft; Schienenverkehr; Verkehrssystem; Industrialisierung; Wirtschaftstheorie; Eisenbahn; Infrastruktur; Verkehrsinfrastruktur; Stadt; Güterverkehr; Wirtschaftsgeschichte; Eisenbahngeschichte; Unternehmensgeschichte; Eisenbahnnetz; Transportsystem; Eisenbahngesetz